2017
DOI: 10.1371/journal.pone.0174933
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of reference genes for quantitative real-time PCR studies in long yellow daylily, Hemerocallis citrina Borani

Abstract: Gene expression analysis using reverse transcription quantitative real-time PCR (RT-qPCR) requires the use of reference gene(s) in the target species. The long yellow daylily, Hemerocallis citrina Baroni. is rich in beneficial secondary metabolites and is considered as a functional vegetable. It is widely cultivated and consumed in East Asian countries. However, reference genes for use in RT-qPCR in H. citrina are not available. In the present study, six potential reference genes, actin (ACT), AP-4 complex sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…The primers sequences for this gene were GAGCAAGGAAATCACGGCACT (forward primer) and GGAACCTCCAATCCAAACACTGTAC (reverse primer). RT-PCR procedure followed Hou et al (2017). Each sample had three biological and three technical replications.…”
Section: Association Analysis For Blooming Time In 155 Hemerocallis Amentioning
confidence: 99%
“…The primers sequences for this gene were GAGCAAGGAAATCACGGCACT (forward primer) and GGAACCTCCAATCCAAACACTGTAC (reverse primer). RT-PCR procedure followed Hou et al (2017). Each sample had three biological and three technical replications.…”
Section: Association Analysis For Blooming Time In 155 Hemerocallis Amentioning
confidence: 99%
“…Thus, the selection of appropriate reference genes and design of specific primers are prerequisites for ensuring the accuracy of qRT-PCR results [ 10 ]. Housekeeping genes are often used as standardized reference genes, but the expression of many housekeeping genes varies greatly in different tissues, different species, and under different environmental conditions [ 7 , 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Daylily has distichously arranged long, linear leaves, and showy flowers, which are borne on short pedicels [1]. The flower buds are commonly used as a vegetable in Asia [2]. Recent studies showed that the flowers of daylily have more antioxidant compounds than other plants, making it an excellent nutraceutical food and sparking a potential for medical use [3,4].…”
Section: Introductionmentioning
confidence: 99%